2018
DOI: 10.4049/jimmunol.1701465
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 Modulates Acute Graft-versus-Host Disease by Impacting T Cell Expansion, Migration, and Effector Function

Abstract: MicroRNA-155 (miR-155) is a small noncoding RNA critical for the regulation of inflammation as well as innate and adaptive immune responses. MiR-155 has been shown to be dysregulated in both donor and recipient immune cells during acute graft-versus-host disease (aGVHD). We previously reported that miR-155 is upregulated in donor T cells of mice and humans with aGVHD and that mice receiving miR-155-deficient (miR155) splenocytes had markedly reduced aGVHD. However, molecular mechanisms by which miR-155 modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…Lack of miR155 leads to the impairment of CD4 ؉ and CD8 ؉ T cell recruitment in the livers and spleens of L. donovani-infected mice. It is well known that miR155 deficiency leads to decreased trafficking of CD4 ϩ and CD8 ϩ T cells in various viral infections, like coronavirus (19) and herpes simplex encephalitis (20), as well as under other conditions, like acute graft-versus-host disease (21). It also has been shown that miR155 is highly expressed on regulatory T cells and is a direct target for Foxp3 (22).…”
Section: Resultsmentioning
confidence: 99%
“…Lack of miR155 leads to the impairment of CD4 ؉ and CD8 ؉ T cell recruitment in the livers and spleens of L. donovani-infected mice. It is well known that miR155 deficiency leads to decreased trafficking of CD4 ϩ and CD8 ϩ T cells in various viral infections, like coronavirus (19) and herpes simplex encephalitis (20), as well as under other conditions, like acute graft-versus-host disease (21). It also has been shown that miR155 is highly expressed on regulatory T cells and is a direct target for Foxp3 (22).…”
Section: Resultsmentioning
confidence: 99%
“…Individual mice were ear tagged and graded (on a scale from 0 to 8) twice a week. Mice who reached an aGVHD score of more than or equal to 7 were very sick and were euthanized and their tissues harvested (86,87). GVHD was also assessed by detailed histopathology analysis of H&E-stained liver and gut tissues using a previously reported scoring system with a range of 0 (absence of signs of GVHD) to 4 (maximal GVHD damage) (88).…”
Section: Methodsmentioning
confidence: 99%
“…MiR155 upregulation has been observed in immune cells and in EVs in specimens from patients with evidence of intestinal GvHD (83) and in rodent GvHD experimental models (82). It has been shown that the dysregulation of miR155 in mouse model drives T H 1 proinflammatory T-cell phenotype (84). In this context, the infusion of EVs loaded with anti-miR155 in preclinical models reduced differentiation toward T H 1, T H 9, and T H 17 cells and skewed differentiation toward T H 2 and Treg cells, thus ameliorating the manifestations of GvHD and increasing mice survival (85).…”
Section: Ev Applications In Gvhdmentioning
confidence: 99%